Successful Management of Repeat Breeder Marwari Mare Due to Post Breeding Endometritis - Sutaria, Tarun; Chaudhari, Ravji; Sutaria , Prajwalita; Chaudhari , Chandrakant (The Indian Journal of Animal Reproduction, 2025)
An 11-year-old Marwari mare with a history of repeated unsuccessful conception despite normal cyclicity over three years was presented. Transrectal ultrasound revealed large follicles on the left ovary, uterine edema, and intrauterine fluid. Endometrial cytology and antibiotic sensitivity tests yielded negative results. The mare received treatment with Oxytocin, Gentamicin, and Tolfenamic Acid during estrus, along with GnRH post-breeding. Close monitoring during pre- and post-breeding led to a successful pregnancy, illustrating that appropriate evaluations and treatments can address post-breeding endometritis in repeat breeders.